Placebos in primary care? a nominal group study explicating UK GP and patient views of six theoretically plausible models of placebo practice. Issue 2 (18th February 2020) - Ratnapalan, Mohana; Coghlan, Beverly; Tan, Mengxin; Everitt, Hazel; Geraghty, Adam W A; Little, Paul; Lewith, George; Bishop, Felicity L
Abstract : Objectives: To better understand which theoretically plausible placebogenic techniques might be acceptable in UK primary care. Design: A qualitative study using nominal group technique and thematic analysis. Participants took part in audio-recorded face-to-face nominal groups in which the researcher presented six scenarios describing the application in primary care of theoretically plausible placebogenic techniques: (1) Withholding side effects information, (2) Monitoring, (3) General practitioner (GP) endorsement, (4) Idealised consultation, (5) Deceptive placebo pills and (6) Open-label placebo pills. Participants voted on whether they thought each scenario was acceptable in practice and discussed their reasoning. Votes were tallied and discussions transcribed verbatim. Setting: Primary care in England. Participants: 21 GPs in four nominal groups and 20 'expert patients' in five nominal groups. Results: Participants found it hard to decide which practices were acceptable and spoke about needing to weigh potential symptomatic benefits against the potential harms of lost trust eroding the therapeutic relationship. Primary care patients and doctors felt it was acceptable to harness placebo effects in practice by patient self-monitoring (scenario 2), by the GP expressing a strongly positive belief in a therapy (scenario 3) and by conducting patient-centred, empathic consultations (scenario 4). Deceptive placebogenic practices (scenarios 1 and 5) were unacceptable to most groups. Patient and GP groups expressed a diverse range of opinions about open-label placebo pills. Conclusions: Attempts to harness placebo effects in UK primary care are more likely to be accepted and implemented if they focus on enhancing positive patient-centred communication and empathic relationships. Using placebos deceptively is likely to be unacceptable to both GPs and patients. Open-label placebos also do not have clear support; they might be acceptable to some doctors and patients in very limited circumstances—but further evidence, clear information and guidance would be needed.